2023
DOI: 10.11591/ijece.v13i3.pp3170-3177
|View full text |Cite
|
Sign up to set email alerts
|

Medical image encryption techniques: a technical survey and potential challenges

Abstract: <span lang="EN-US">Among the most sensitive and important data in telemedicine systems are medical images. It is necessary to use a robust encryption method that is resistant to cryptographic assaults while transferring medical images over the internet. Confidentiality is the most crucial of the three security goals for protecting information systems, along with availability, integrity, and compliance. Encryption and watermarking of medical images address problems with confidentiality and integrity in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The researchers in 2023 demonstrated that the encryption of medical images and records and protecting the patient's privacy are legal responsibilities that the existing algorithms may not achieve optimally [16].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers in 2023 demonstrated that the encryption of medical images and records and protecting the patient's privacy are legal responsibilities that the existing algorithms may not achieve optimally [16].…”
Section: Related Workmentioning
confidence: 99%
“…The model makes use of both symmetric and uneven encryption calculation (AES and ECC) to enhance information security against intruders, preventing illegal access to natural resources, improving privacy and time taken to perform cryptographic tasks, and further developing the trust level of the client in the cloud and accelerating the use of more modest keys of ECC in the cryptographic interaction. Table 1 represents the comparative analysis of related work in detail papers [14][15][16][17][18][19][20] Table 1: Comparative analysis of related work Refs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays we have many patients with discomfort in their care and this is reflected in any health center in the world, medical congestion is very frequent since the long waiting list in health centers can be a delay and problem for doctors, surgeries, or consultations with specialists are a headache for patients who require short and urgent care [1]. Lack of specialists contributes to a major problem, showing patient overload and great difficulty in medical care [2]- [5]. India has a high population density in its health services which are overloaded with patients, showing a total collapse in hospitals and more so for COVID-19 diseases or similar symptoms treated in health centers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ciphering images is the process of protecting them by altering their pixels in a way that makes them indecipherable. It protects image confidentiality and integrity, particularly when the images are sensitive and confidential, as is the military case [1] and medical images [2], [3]. Perturbations in ciphering steps complicate the statistical relationships between original and ciphered images and make predicting them difficult.…”
Section: Introductionmentioning
confidence: 99%